Outside and As If - Judith Wolin (Oz, 1988)
The invitation to write this article was accompanied by a sketch definition of narrative architecure which included the suggestion ... "Many architects have something to say in their architecture, a story to tell. There are a variety of means architects employ in expressing their own, or their clients values, thoughts, wishes, beliefs, and desires...